ASESMEN BERBASIS APEM (AI UNTUK PEMBELAJARAN): SOLUSI UNTUK MENINGKATKAN UMPAN BALIK PEMBELAJARAN DI KELAS 4 SDN BUAHKAPAS - Mulyani, Yani (Cahaya Ilmu Bangsa Institute, 2024)
This study examines the application of APEM-Based Assessment (AI for Learning) in the 4th grade of SDN Buahkapas as a solution to improve feedback in the learning process. Traditional assessment methods are often homogeneous and fail to meet the diverse learning needs of students. Therefore, the use of artificial intelligence (AI) in assessment is expected to provide faster, more accurate, and personalized feedback. This research uses a library study approach to explore how APEM can be integrated into the learning and assessment process. The results show that APEM improves student engagement, provides more relevant feedback, and facilitates teachers in designing lessons. This study also identifies challenges such as infrastructure readiness and teacher training. With proper support, APEM has great potential to enhance the quality of education in elementary schools. Keywords: APEM-Based Assessment, Artificial Intelligence, Learning Feedback;